Relationship between C9orf72 repeat size and clinical phenotype. (June 2017) - Van Mossevelde, Sara; van der Zee, Julie; Cruts, Marc; Van Broeckhoven, Christine
Abstract : Patient carriers of a C9orf72 repeat expansion exhibit remarkable heterogeneous clinical and pathological characteristics suggesting the presence of modifying factors. In accordance with other repeat expansion diseases, repeat length is the prime candidate as a genetic modifier. Observations of earlier onset ages in younger generations of large families suggested a mechanism of disease anticipation. Yet, studies of repeat size and onset age have led to conflicting results. Also, the correlation between repeat size and diagnosis is poorly understood. We review what has been published regarding C9orf72 repeat size as modifier for phenotypic characteristics. Conclusive evidence is lacking, partly due to the difficulties in accurately defining the exact repeat size and the presence of repeat variability due to somatic mosaicism.